Rules Infants Look By: Testing the Assumption of Transitivity in Visual Salience. (2nd October 2017) - Kibbe, Melissa M.; Kàldy, Zsuzsa; Blaser, Erik
Abstract : What drives infants' attention in complex visual scenes? Early models of infant attention suggested that the degree to which different visual features were detectable determines their attentional priority. Here, we tested this by asking whether two targets—defined by different features, but each equally salient when evaluated independently—would drive attention equally when pitted head‐to‐head. In Experiment 1, we presented 6‐month‐old infants with an array of Gabor patches in which a target region varied either in color or spatial frequency from the background. Using a forced‐choice preferential‐looking method, we measured how readily infants fixated the target as its featural difference from the background was parametrically increased. Then, in Experiment 2, we used these psychometric preference functions to choose values for color and spatial frequency targets that were equally salient (preferred), and pitted them against each other within the same display. We reasoned that if salience is transitive, then the stimuli should be iso‐salient and infants should therefore show no systematic preference for either stimulus. On the contrary, we found that infants consistently preferred the color‐defined stimulus. This suggests that computing visual salience in more complex scenes needs to include factors above and beyond local salience values.